The Role of Information Systems Capabilities in Enhancing the Organizational Performance - Laith Tashtoush (Universitas Bina Darma, 2021)
The literature supports that information systems improve the effective performance of any organization and gain a competitive advantage for their success in the business environment. Therefore, the scholars should do more studies that focus on how to enhance organizational performance to let corporations to sustain their competitive advantage. This study aims to empirically investigate the mediating role of competitive advantage with information systems capabilities and organizational performance among managers and department heads working in Jordanian industrial corporations. The study population consisted of all managers and department heads working in 20 Jordanian industrial corporations. The analysis of the data included the calculation of descriptive statistics as well as structural equation modeling, regression analysis, correlation analysis, and factor analysis. The study results showed that information systems capabilities, competitive advantage, and organizational performance were statistically significant. In addition, the result revealed that information system capabilities through competitive advantage influence organizational performance. The study model developed to provide the relationships of information systems capabilities through competitive advantage that can be used by Jordanian industrial corporations as evidence of a positive impact on organizational performance of managers and heads of departments in their corporations.